2016
DOI: 10.1002/alr.21890
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the number of allergen sensitizations and immunoglobulin E: monosensitization vs polysensitization

Abstract: IgE level can be used to predict monosensitization vs polysensitization. There is a moderate correlation between total IgE sensitization and the number of positive allergen sensitizations, as well as allergen class-weighted sensitizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…As has been reported in other studies, most patients in our cohort were oligosensitized [34, 35]. Based on the discussion above on the role of HDM in allergy in Alberta, it is interesting that HDM was the most common mono-sensitizing allergen in our study, as has been reported before [36]. The retrospective nature of our study and the lack of clinical information for the tested subjects do not allow us to make conclusions on the significance of this observation.…”
Section: Discussionsupporting
confidence: 79%
“…As has been reported in other studies, most patients in our cohort were oligosensitized [34, 35]. Based on the discussion above on the role of HDM in allergy in Alberta, it is interesting that HDM was the most common mono-sensitizing allergen in our study, as has been reported before [36]. The retrospective nature of our study and the lack of clinical information for the tested subjects do not allow us to make conclusions on the significance of this observation.…”
Section: Discussionsupporting
confidence: 79%
“…The absence of statistical significance in several of the comparisons might be due to the insufficiency of the sample number considered for the analysis or the technical instability of our protease assays. Serum total IgE reflects the degree of allergen sensitization [31,32]. Serum TARC is the most sensitive clinical biomarker of AD [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that total IgE is widely variable among patients with allergic diseases, particularly in patients with polysensitization. 33 Overall, the ideal management of allergic disease and anaphylaxis is strict avoidance of the trigger, if known. Hence, an attempt should always be made to identify the culprit, particularly in difficult cases or patients with a history of allergic episodes.…”
Section: Discussionmentioning
confidence: 99%